Anthropometric and strength characteristics of rugby place kickers - Bezodis, N. E.; Atack, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The musculoskeletal demands of rugby place kicking are of interest to coaches from both a performance and an injury perspective. Specific musculoskeletal model inputs are required to accurately investigate these demands. This study determined selected anthropometric and strength characteristics of professional and amateur place kickers from photo-based measurements and vertical jumps. All segmental inertia characteristics were similar between the two groups aside from the torso moment of inertia. Professional players displayed superior jump strength measures compared with the amateurs. The kickers' inertia and strength characteristics also differed from commonly used values obtained from physically active males and male soccer players. Careful consideration of input parameters is required when developing musculoskeletal models of rugby kickers.